2018
DOI: 10.4236/fns.2018.910083
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of <i>Bunchosia glandulifera</i> Fruit at Different Ripening Stages

Abstract: Bunchosia glandulifera belongs to the family Malpighiaceae and is popularly known as "caferana" in the city of Santo Antonio da Patrulha. The fruits have a high economic value and their inclusion in the diet has health benefits. They are natural sources of antioxidants because of the presence of bioactive compounds. However, their chemical composition can be influenced by the maturation process. This study aims to evaluate the changes in the bioactive antioxidant compounds in the pulp and seeds of B. glandulif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
8
0
3
Order By: Relevance
“…Previous studies reported the presence of caffeine in Bunchosia glandulifera fruit, which is consistent with our findings [ 32 , 60 ]. However, to our knowledge, this is the first report for the detection of trigonelline and harmaline in Bunchosia , while trigonelline was previously isolated from the leaves of Niedenzuella multiglandulosa (Malpighiaceae) [ 61 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Previous studies reported the presence of caffeine in Bunchosia glandulifera fruit, which is consistent with our findings [ 32 , 60 ]. However, to our knowledge, this is the first report for the detection of trigonelline and harmaline in Bunchosia , while trigonelline was previously isolated from the leaves of Niedenzuella multiglandulosa (Malpighiaceae) [ 61 ].…”
Section: Resultssupporting
confidence: 94%
“…During the ripening process, the level of flavonoids in the fruit increased significantly. This could be due to the carotenoid synthesis during the color transition from green to yellow, which is correlated to increased flavonoid quantity [ 32 ]. The difference in total phenolic and flavonoid content values may occur due to the difference in plant parts studied.…”
Section: Resultsmentioning
confidence: 99%
“…Em 30 dias, aproximadamente, o fruto amadurece e as duas últimas etapas da maturação acontecem em um período de 3 a 4 dias (BLANK et al, 2018).…”
Section: Introductionunclassified
“…Além de fornecer compostos bioativos, a fruta café-do-amazonas contém diversos nutrientes, sendo uma excelente fonte de macronutrientes essenciais e micronutrientes, podendo ser amplamente incorporada na alimentação dos seres humanos (BLANK et al, 2018).…”
Section: Introductionunclassified